2019
DOI: 10.1016/j.jcot.2019.04.018
|View full text |Cite|
|
Sign up to set email alerts
|

Tip-apex distance and other predictors of outcome in cephalomedullary nailing of unstable trochanteric fractures

Abstract: Background: Cephalomedullary nails are presently the gold standard in management of unstable trochanteric fractures. The tip-apex distance (TAD) is one of the most important factors that determines success or failure of fixation, but was described originally in context of an extramedullary hip screw. Cephalomedullary nails use a different biomechanical approach to fixation; and it is hypothesized that the TAD rule may not apply similarly with these. The aim of this study is to assess whether a high TAD correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 27 publications
(35 reference statements)
3
16
0
Order By: Relevance
“…Mean TAD total was 22.8mm while TAD ap and TAD lateral was 11.8 and 11.0mm respectively ( Table IV ). TAD has been poorly studied in biaxial cephalomedullary implants (having two screws) such as ours and currently there is no proven or recommended TAD for such implants 15 , 16 . Most frequent position of lag screw was charted in inferior-central zone in 95 cases ( Fig.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Mean TAD total was 22.8mm while TAD ap and TAD lateral was 11.8 and 11.0mm respectively ( Table IV ). TAD has been poorly studied in biaxial cephalomedullary implants (having two screws) such as ours and currently there is no proven or recommended TAD for such implants 15 , 16 . Most frequent position of lag screw was charted in inferior-central zone in 95 cases ( Fig.…”
Section: Resultsmentioning
confidence: 92%
“…They concluded that a combination of high TAD, suboptimal position of implant and poor restoration of neck shaft angle may predispose to cut-out. However, achieving TAD within safe limits didn’t appear to influence screw and device migration in dual screw nails 16 . Another technical aspect of note is the length of anti-rotation screw.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, identifying predictors of failure is particularly relevant. Though much has been published regarding predictors of failure of extramedullary implants, [4][5][6][7] nail failure has not been extensively studied [8][9][10][11]. Since the biomechanical behavior of extramedullary implants differs from that of intramedullary implants, predictors of failure may also be different.…”
Section: Introductionmentioning
confidence: 99%
“…However, the overall failure rate of fixation operations for unstable femoral trochanteric fractures is 3-12%. 5 - 7 …”
Section: Introductionmentioning
confidence: 99%